Elderly Helping Other Elderly: A Comparative Study of Family Caregiver Burden Between Patients With Dementia or Cancer at the End of Life. Issue 1 (2nd January 2022) - Spatuzzi, Roberta; Vespa, Anna; Fabbietti, Paolo; Ricciuti, Marcello; Rosati, Gerardo; Guariniello, Lorella; Verrastro, Maria Antonietta Flavia; Attademo, Luigi; Giulietti, Maria Velia
Abstract: A new reality is being observed around the world as the population ages: family caregivers, who are themselves older adults helping their ill older relatives. The aim of this study is to assess the burden of the older family caregiver assisting older patients in his or her end-of-life who are suffering from dementia or cancer. In this context, the elderly person is involved in the dual role of patient and caregiver. In this comparative study, a total of 87 older family caregivers (age ≥ 65 years) completed the Caregiver Burden Inventory (CBI) measurement. The sample was divided into 2 subgroups based on the individuals' advanced disease: Alzheimer's disease (AD) or cancer. Compared to cancer caregivers, the AD subgroup reported significantly higher scores in the CBI-emotional subscale ( P = 0.006), confirmed by the evaluation of the generalized linear model (multivariate). There were no significant differences in the other CBI subscales and overall scores. According to the findings of this study, elderly who help elderly with AD are at a higher risk of experiencing an emotional burden than cancer caregivers. This data could be considered in designing interventions to reduce the caregiver burden of older family caregivers as they provide informal end-of-life care.